Optimization of Boost Inductor Size Using Multiple DC-DC Boost Converter Configurations for Multilevel Inverter Applications - Abdul Talib, `Aliah Afiqah; Ponniran, Asmarashid (Evolution in Electrical and Electronic Engineering, 2023)
This study proposes using multiple non-isolated DC-DC boost converters to optimize the performance of boost inductors in multilevel inverter (MLI) systems. A bulky boost inductor can increase the overall weight of the multilevel inverter system. The configuration selection and converter design are crucial aspects in achieving these objectives. The number and arrangement of boost converters are based on the desired multilevel inverter topology, with each converter designated based on input voltage, output voltage, current rating, and switching frequency. Advanced software, PLECS software tools, is used for computation analysis. The output voltage gained is slightly different from expected, but a snubber circuit is used to minimize voltage spikes. Optimizing boost inductor size offers potential benefits, such as space-saving in applications with limited space for component placement. Additionally, smaller inductors have small core losses, leading to improved efficiency in boost converter design.